Effectiveness of Government Accountability in Sustainable Development-Based Urban Waste Management (SDGs): Case Study of the Bantar Gebang Integrated Waste Management Site - Rayi Kharisma Rajib; Arya Wiarnata; Sheila Nasywa Razani (Adagium: Jurnal Ilmiah Hukum, 2026)
Urban waste management at the Bantar Gebang Integrated Waste Management Site (TPST) faces various challenges in achieving sustainable development while fulfilling government responsibilities. This study analyzes the fulfillment of the environmental dimensions of the Sustainable Development Goals (SDGs), together with the legal constraints and implications of the accountability of the Provincial Government of DKI Jakarta. The findings show that the fulfillment of the SDGs, particularly Goals 11, 12, and 13, remains suboptimal because open dumping continues to be prioritized in the waste-management process despite its prohibition under Law Number 18 of 2008. This condition has indirectly contributed to the accumulation of 55 million tons of waste, environmental pollution, and a waste landslide that killed several people in March 2026. The main obstacles to effective waste management include ambiguity in cross-jurisdictional authority between Jakarta and Bekasi, dependence on environmentally unfriendly technology, and weak administrative-law enforcement. The legal implications include non-compliance with administrative sanctions, the potential for class actions and citizen lawsuits under Law Number 32 of 2009, and the designation of the former Head of the DKI Jakarta Environmental Agency as a criminal suspect. The study concludes that government accountability remains ineffective and requires systemic and governance improvements, including source-based waste reduction, optimization of environmentally friendly technology, and stronger interregional coordination.